Faktor – Faktor Yang Mempengaruhi Ekspor Cocoa Powder Indonesia Ke China - Arif Munandar Harahap; Yeniwati Yeniwati (Universitas Negeri Padang, 2023)
This study aims to analyze the factors that influence Indonesia's cocoa powder exports to China. The data used in this study is time series data from 2008 M01 to 2019 M04. Data from the International Monetary Fund (IMF), trade statistics for international business development (trademap.org), the Indonesian ministry of agriculture, and the international cocoa organization (ICCO). This research is quantitative research with an ECM analysis model. The results showed that the international cocoa bean price and industrial production index had a positive effect on cocoa powder exports, but the international cocoa bean price variable was not significant in both the short and long term. On the other hand, the exchange rate variable has a large negative impact on Indonesia's cocoa powder exports to China in the long term and a small positive impact in the short term.